Assessment of risk communication and community engagement interventions during the Marburg virus disease outbreak in Kagera region, Northwestern Tanzania - Mololo Noah Mwanjala; Emmanuel Mnkeni; Mikidadi Issanudia Mtalika; Marcelina Mponela; Atuganile Musyani; George Mrema; Amour Seleman; Catherine Gitige; Kokuhabwa Mukurasi; Gloria Macha; Hussein Mohamed; Pius Horumpende; et al. (Bulletin of the National Research Centre)
Abstract Background Marburg virus disease (MVD) is a deadly illness caused by the zoonotic Marburg virus, which has led to outbreaks with fatality rates up to 100% in some African countries. On March 21, 2023, Tanzania had its first MVD outbreak, resulting in nine cases and six deaths, leading to a fatality rate of 66.7%. Following that, the Risk Communication and Community Engagement (RCCE) approach was promptly initiated to create community awareness regarding the MVD. A descriptive cross-sectional assessment was conducted in May 2023 in Bukoba District Council and Bukoba Municipal Council in the Kagera region to document the community awareness and sources of information regarding MVD during the outbreak. Data were collected using a structured questionnaire developed using the WHO COVID-19 RCCE Rapid Quantitative Assessment Tool. Descriptive analysis was conducted using Microsoft Excel 2021. Results There were a total of 714 community respondents, of whom 456 (63.9%) were from Bukoba District Council. The majority 628 (88%) were aged 18 years and above. There were 393 (55%) females, and 407 (57%) of respondents had completed primary education. All respondents reported being informed about MVD through different channels, with 588 (82.4%) receiving information from Community Health Workers. Most of them 573 (80.3%) were satisfied with implemented RCCE interventions, 651 (91.2%) perceived MVD to be an extremely severe disease, and 698 (97.76%) mentioned hand washing as one of the recommended preventive measures. Conclusions During the Marburg virus disease outbreak response, where risk communication and community engagement interventions were implemented, the community was aware of the Marburg virus disease and community health workers emerged as the most frequently mentioned channel of communication during the outbreak.